Design of a broadly reactive Lyme disease vaccine - Kamp, Heather D; Swanson, Kurt A; Wei, Ronnie R; Dhal, Pradeep K; Dharanipragada, Ram; Kern, Aurelie; Sharma, Bijaya; Sima, Radek; Hajdusek, Ondrej; Hu, Linden T; Wei, Chih-Jen; Nabel, Gary J (NPJ vaccines, 2020)
A growing global health concern, Lyme disease has become the most common tick-borne disease in the United States and Europe. Caused by the bacterial spirochete Borrelia burgdorferi sensu lato (sl), this disease can be debilitating if not treated promptly. Because diagnosis is challenging, prevention remains a priority; however, a previously licensed vaccine is no longer available to the public. Here, we designed a six component vaccine that elicits antibody (Ab) responses against all Borrelia strains that commonly cause Lyme disease in humans. The outer surface protein A (OspA) of Borrelia was fused to a bacterial ferritin to generate self-assembling nanoparticles. OspA-ferritin nanoparticles elicited durable high titer Ab responses to the seven major serotypes in mice and non-human primates at titers higher than a previously licensed vaccine. This response was durable in rhesus macaques for more than 6 months. Vaccination with adjuvanted OspA-ferritin nanoparticles stimulated protective immunity from both B. burgdorferi and B. afzelii infection in a tick-fed murine challenge model. This multivalent Lyme vaccine offers the potential to limit the spread of Lyme disease.
Keywords: Immunology; Infectious diseases; Vaccines